MODEL PEMBELAJARAN SAINS BERBASIS BUDAYA LOKAL - Sri Anita Dewi; Muhammad Syukri (Jurnal Payung Sekaki : Kajian Keislaman, 2025)
This study aims to analyze the needs assessment of students in learning science (IPA) in junior high school, which will be used as a basis for designing a culture-based science learning model for the development of basic science competencies and local wisdom values. The teachers sampled in this study were 30 junior high school science teachers. Data were collected through literature review, questionnaires, and interviews. The data were analyzed descriptively. Based on the results of data analysis and discussion, the following conclusions can be drawn. 1) In grades VII and VIII, there are 11 basic competencies (KD) that can be developed in local culture-based science learning. 3) The methods suitable for local culture-based science learning are investigation/experimentation, field observation, and discussion. 4) Suitable learning resources to support science learning are the natural and socio-cultural environment, textbooks, audio-visual materials, and the internet. 5) Suitable learning designs to be developed include the following steps: initial activities, investigation from various perspectives (exploration), elaboration, confirmation, and final activities.